TLMaths BUMPER Worksheet of Differential Equations (Separation of Variables)
TLMaths BUMPER Worksheet of Differential Equations (Separation of Variables)
TLMaths BUMPER Worksheet of Differential Equations (Separation of Variables)
Prerequisites: Reciprocal Trigonometric Functions, Double Angle Formulae, Integrals of 𝑒 "# , sin 𝑘𝑥, cos 𝑘𝑥,
sec , 𝑘𝑥, sin, 𝑘𝑥, cos , 𝑘𝑥, Integration by Substitution, Integration by Parts, Partial Fractions.
• Solutions show the separation of variables and then the general solution.
• Care has been taken to avoid ± in general solutions.
• Not all general solutions have been rearranged to make 𝑦 the subject.
• 𝑐0 is used to represent the constant of integration in each case.
• Nested fractions have been avoided in the general solution.
01 02
𝑑𝑦 𝑥 𝑑𝑦 𝑥 ,
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑦
03 04
𝑑𝑦 𝑥 3 𝑑𝑦 𝑥 4
= =
𝑑𝑥 𝑦 , 𝑑𝑥 𝑦 3
05 06
𝑑𝑦 𝑑𝑦
= 𝑥𝑦 = 𝑥,𝑦
𝑑𝑥 𝑑𝑥
07 08
𝑑𝑦 1 𝑑𝑦
= 𝑥3𝑦, = 𝑦3
𝑑𝑥 𝑥 4 𝑑𝑥
09 10
𝑑𝑦 𝑦 𝑑𝑦
= 𝑥 = 𝑦,
𝑑𝑥 𝑥 𝑑𝑥
11 12
𝑑𝑦 𝑦 3 𝑑𝑦
= 𝑥3 = 𝑦4
𝑑𝑥 𝑥 , 𝑑𝑥
13 14
𝑑𝑦 𝑥 1 𝑑𝑦 1
= =
𝑑𝑥 𝑦 + 1 𝑥 + 1 𝑑𝑥 𝑦
15 16
𝑑𝑦 𝑑𝑦
= 𝑥(𝑦 + 1) = (𝑥 + 1)𝑦
𝑑𝑥 𝑑𝑥
17 18
𝑑𝑦 𝑦 𝑑𝑦
= 𝑥 =𝑦+1
𝑑𝑥 𝑥 + 1 𝑑𝑥
19 20
𝑑𝑦 𝑑𝑦 𝑥𝑦
𝑥 = (𝑥 + 1)𝑦 =
𝑑𝑥 𝑑𝑥 𝑦 + 1
21 22
𝑑𝑦 (𝑥 , − 3)𝑦 , 1 𝑑𝑦 𝑦3
= = ,
𝑑𝑥 𝑥 5𝑥 𝑑𝑥 𝑦 − 1
23 24
𝑑𝑦 (𝑥 3 + 3𝑥 + 9)𝑦 3 𝑑𝑦
= 𝑥= = 2(𝑥 ? − 𝑥 3 + 8)𝑦 4
𝑑𝑥 𝑥, 𝑑𝑥
25 26
𝑑𝑦 (𝑥 + 2), 𝑦 4 1 𝑑𝑦 𝑦 =
= =
𝑑𝑥 𝑥 (2𝑥 − 3), 𝑑𝑥 𝑥
27 28
𝑑𝑦 (5𝑥 − 4), 𝑦 3 𝑑𝑦
= 𝑥3 = (9𝑥 + 2), 𝑦 ?
𝑑𝑥 𝑥, 𝑑𝑥
29 30
𝑑𝑦 (3𝑥 + 2), 𝑦 4 𝑑𝑦
= 𝑥 , (5𝑦 − 4), = (4𝑥 − 5), 𝑦 =
𝑑𝑥 𝑥 3 (3𝑦 − 2), 𝑑𝑥
31 32
𝑑𝑦 √𝑥 𝑑𝑦
= 𝑥D = E𝑦
𝑑𝑥 𝑦 D 𝑑𝑥
33 34
𝑑𝑦 𝑥 𝑑𝑦 𝑦
=F =G
𝑑𝑥 𝑦 𝑑𝑥 𝑥
35 36
𝑑𝑦 H 𝑥 𝑑𝑦 H 𝑦
=F =G
𝑑𝑥 𝑦 𝑑𝑥 𝑥
37 38
𝑑𝑦 𝑒 # 𝑑𝑦 𝑒 I
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑥
39 40
1 𝑑𝑦 1 𝑑𝑦
#
= I = 𝑒 ,#JI
𝑒 𝑑𝑥 𝑒 𝑑𝑥
41 42
𝑑𝑦 𝑒 I 𝑑𝑦
= = 𝑒 ,IJ#
𝑑𝑥 𝑒 # 𝑑𝑥
43 44
𝑑𝑦 𝑑𝑦
= 𝑒 #𝑒I = 𝑒 ,#KI
𝑑𝑥 𝑑𝑥
45 46
𝑑𝑦 𝑒 J3# 𝑑𝑦 𝑒 J4I
= =
𝑑𝑥 𝑒 J4I 𝑑𝑥 𝑒 J,#
47 48
𝑑𝑦 sin 𝑥 𝑑𝑦 cos 𝑥
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑦
49 50
𝑑𝑦 sin 2𝑥 𝑑𝑦 1
= sec 3𝑥 =
𝑑𝑥 2𝑦 𝑑𝑥 3𝑦
51 52
𝑑𝑦 cos 𝑥 𝑑𝑦 sin 𝑥
= =
𝑑𝑥 sin 𝑦 𝑑𝑥 cos 𝑦
P 𝑦 𝑑𝑦 = P 𝑥 𝑑𝑥 P 𝑦 𝑑𝑦 = P 𝑥 , 𝑑𝑥
𝑦 , = 𝑐0 + 𝑥 , 2
𝑦 , = 𝑐0 + 𝑥 3
3
03 04
𝑑𝑦 𝑥 3 𝑑𝑦 𝑥 4
= =
𝑑𝑥 𝑦 , 𝑑𝑥 𝑦 3
P 𝑦 , 𝑑𝑦 = P 𝑥 3 𝑑𝑥 P 𝑦 3 𝑑𝑦 = P 𝑥 4 𝑑𝑥
4
H 3 𝑦 4 = 𝑐0 + 𝑥 =
𝑦 = F𝑐0 + 𝑥 4 5
4
05 06
𝑑𝑦 𝑑𝑦
= 𝑥𝑦 = 𝑥,𝑦
𝑑𝑥 𝑑𝑥
1 1
P 𝑑𝑦 = P 𝑥 𝑑𝑥 P 𝑑𝑦 = P 𝑥 , 𝑑𝑥
𝑦 𝑦
0 Q 0 H
𝑦 = 𝑐0 𝑒 ,# 𝑦 = 𝑐0 𝑒 3#
07 08
𝑑𝑦 1 𝑑𝑦
= 𝑥3𝑦, = 𝑦3
𝑑𝑥 𝑥 4 𝑑𝑥
1 1
P 𝑑𝑦 = P 𝑥 3 𝑑𝑥 P 𝑑𝑦 = P 𝑥 4 𝑑𝑥
𝑦, 𝑦3
4 5
𝑦= 𝑦, =
𝑐0 − 𝑥 4 𝑐0 − 2𝑥 =
09 10
𝑑𝑦 𝑦 𝑑𝑦
= 𝑥 = 𝑦,
𝑑𝑥 𝑥 𝑑𝑥
1 1 1 1
P 𝑑𝑦 = P 𝑑𝑥 P ,
𝑑𝑦 = P 𝑑𝑥
𝑦 𝑥 𝑦 𝑥
𝑦 = 𝑐0 𝑥 1
𝑦=
𝑐0 − ln 𝑥
1 1 1 1
P 𝑑𝑦 = P , 𝑑𝑥 P 4
𝑑𝑦 = P 3 𝑑𝑥
𝑦 3 𝑥 𝑦 𝑥
𝑥
𝑦, = H 2𝑥 ,
2 + 𝑐0 𝑥 𝑦= F
3 + 𝑐0 𝑥 ,
13 14
𝑑𝑦 𝑥 1 𝑑𝑦 1
= =
𝑑𝑥 𝑦 + 1 𝑥 + 1 𝑑𝑥 𝑦
P(𝑦 + 1) 𝑑𝑦 = P 𝑥 𝑑𝑥 P 𝑦 𝑑𝑦 = P(𝑥 + 1) 𝑑𝑥
𝑦 , + 2𝑦 = 𝑐0 + 𝑥 , 𝑦 , = 𝑐0 + 𝑥 , + 2𝑥
15 16
𝑑𝑦 𝑑𝑦
= 𝑥(𝑦 + 1) = (𝑥 + 1)𝑦
𝑑𝑥 𝑑𝑥
1 1
P 𝑑𝑦 = P 𝑥 𝑑𝑥 P 𝑑𝑦 = P(𝑥 + 1) 𝑑𝑥
𝑦+1 𝑦
0 Q 0 Q
𝑦 = 𝑐0 𝑒 ,# − 1 𝑦 = 𝑐0 𝑒 ,# K#
17 18
𝑑𝑦 𝑦 𝑑𝑦
= 𝑥 =𝑦+1
𝑑𝑥 𝑥 + 1 𝑑𝑥
1 1 1 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
𝑦 𝑥+1 𝑦+1 𝑥
𝑦 = 𝑐0 (𝑥 + 1) 𝑦 = 𝑐0 𝑥 − 1
19 20
𝑑𝑦 𝑑𝑦 𝑥𝑦
𝑥 = (𝑥 + 1)𝑦 =
𝑑𝑥 𝑑𝑥 𝑦 + 1
1 1 1
P 𝑑𝑦 = P R1 + S 𝑑𝑥 P R1 + S 𝑑𝑦 = P 𝑥 𝑑𝑥
𝑦 𝑥 𝑦
𝑦 = 𝑐0 𝑥𝑒 # 1
𝑦 + ln 𝑦 = 𝑐0 + 𝑥 ,
2
1 3 1 1
P ,
𝑑𝑦 = P R𝑥 − S 𝑑𝑥 P R − 3 S 𝑑𝑦 = P 5𝑥 𝑑𝑥
𝑦 𝑥 𝑦 𝑦
2 1 5
𝑦= ln 𝑦 − = 𝑐0 + 𝑥 ,
𝑐0 + 6 ln 𝑥 − 𝑥 , 2𝑦 , 2
23 24
𝑑𝑦 (𝑥 3 + 3𝑥 + 9)𝑦 3 𝑑𝑦
= 𝑥= = 2(𝑥 ? − 𝑥 3 + 8)𝑦 4
𝑑𝑥 𝑥, 𝑑𝑥
1 3 9 1 1 8
P 𝑑𝑦 = P R𝑥 + + , S 𝑑𝑥 P 4
𝑑𝑦 = P R𝑥 − , + = S 𝑑𝑥
𝑦 3 𝑥 𝑥 2𝑦 𝑥 𝑥
𝑥
𝑦, = H 𝑥4
𝑐0 𝑥 + 18 − 𝑥 3 − 6𝑥 ln 𝑥 𝑦= F 4
𝑐0 𝑥 − 3𝑥 ? − 6𝑥 3 + 12
25 26
𝑑𝑦 (𝑥 + 2), 𝑦 4 1 𝑑𝑦 𝑦 =
= =
𝑑𝑥 𝑥 (2𝑥 − 3), 𝑑𝑥 𝑥
1 4 1 9
P 𝑑𝑦 = P R𝑥 + 4 + S 𝑑𝑥 P 𝑑𝑦 = P R4𝑥 − 12 + S 𝑑𝑥
𝑦4 𝑥 𝑦 = 𝑥
2 1
H
𝑦= F 𝑦4 =
,
𝑐0 − 3𝑥 − 24𝑥 − 24 ln 𝑥 𝑐0 − 8𝑥 , + 48𝑥 − 36 ln 𝑥
27 28
𝑑𝑦 (5𝑥 − 4), 𝑦 3 𝑑𝑦
= 𝑥3 = (9𝑥 + 2), 𝑦 ?
𝑑𝑥 𝑥, 𝑑𝑥
1 40 16 1 81 36 4
P 𝑑𝑦 = P R25 − + , S 𝑑𝑥 P ?
𝑑𝑦 = P R + , + 3 S 𝑑𝑥
𝑦 3 𝑥 𝑥 𝑦 𝑥 𝑥 𝑥
𝑥
𝑦, = T 𝑥,
𝑐0 𝑥 − 50𝑥 , + 80𝑥 ln 𝑥 + 32 𝑦= F ,
𝑐0 𝑥 − 405𝑥 , ln 𝑥 + 180𝑥 + 10
29 30
𝑑𝑦 (3𝑥 + 2), 𝑦 4 𝑑𝑦
= 𝑥 , (5𝑦 − 4), = (4𝑥 − 5), 𝑦 =
𝑑𝑥 𝑥 3 (3𝑦 − 2), 𝑑𝑥
9 12 4 9 12 4 25 40 16 40 25
PR − 3 + 4 S 𝑑𝑦 = P R + , + 3 S 𝑑𝑥 P R 3 − 4 + = S 𝑑𝑦 = P R16 − + , S 𝑑𝑥
𝑦 , 𝑦 𝑦 𝑥 𝑥 𝑥 𝑦 𝑦 𝑦 𝑥 𝑥
9 6 4 12 2 25 40 4 25
− + , − 3 = 𝑐0 + 9 ln 𝑥 − − − + − = 𝑐0 + 16𝑥 − 40 ln 𝑥 −
𝑦 𝑦 3𝑦 𝑥 𝑥, 2𝑦 , 3𝑦 3 𝑦 4 𝑥
1 1
P 𝑦 D 𝑑𝑦 = P √𝑥 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
E𝑦 𝑥D
U 3 1 ,
𝑦 = G𝑐0 + 6𝑥 , 𝑦 = R𝑐0 − S
14𝑥 V
33 34
𝑑𝑦 𝑥 𝑑𝑦 𝑦
=F =G
𝑑𝑥 𝑦 𝑑𝑥 𝑥
1 1
P 𝑑𝑦 = P 𝑑𝑥
P E𝑦 𝑑𝑦 = P √𝑥 𝑑𝑥 E𝑦 √𝑥
,
, 𝑦 = W𝑐0 + √𝑥X
3 3
𝑦 = R𝑐0 + 𝑥,S
35 36
𝑑𝑦 H 𝑥 𝑑𝑦 H 𝑦
=F =G
𝑑𝑥 𝑦 𝑑𝑥 𝑥
1 1
P H 𝑑𝑦 = P H 𝑑𝑥
H
P E𝑦 𝑑𝑦 = P √𝑥 𝑑𝑥
H
E𝑦 √𝑥
, ,
4 4 𝑦 3 = 𝑐0 + 𝑥 3
𝑦3 = 𝑐0 + 𝑥3
37 38
𝑑𝑦 𝑒 # 𝑑𝑦 𝑒 I
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑥
1 1
P 𝑦 𝑑𝑦 = P 𝑒 # 𝑑𝑥 P I
𝑑𝑦 = P 𝑑𝑥
𝑒 𝑥
𝑦 , = 𝑐0 + 2𝑒 # 1
𝑦 = ln R S
𝑐0 − ln 𝑥
39 40
1 𝑑𝑦 1 𝑑𝑦
#
= I = 𝑒 ,#JI
𝑒 𝑑𝑥 𝑒 𝑑𝑥
P 𝑒 I 𝑑𝑦 = P 𝑒 # 𝑑𝑥 P 𝑒 I 𝑑𝑦 = P 𝑒 ,# 𝑑𝑥
𝑦 = ln(𝑐0 + 𝑒 # ) 𝑦 = ln(𝑐0 + 𝑒 ,# )
1 1 1 1
P I
𝑑𝑦 = P # 𝑑𝑥 P ,I
𝑑𝑦 = P # 𝑑𝑥
𝑒 𝑒 𝑒 𝑒
𝑒# 1 𝑒#
𝑦 = ln Y # Z 𝑦 = ln Y # Z
𝑐0 𝑒 + 1 2 𝑐0 𝑒 + 2
43 44
𝑑𝑦 𝑑𝑦
= 𝑒 #𝑒I = 𝑒 ,#KI
𝑑𝑥 𝑑𝑥
1 1
P 𝑑𝑦 = P 𝑒 # 𝑑𝑥 P 𝑑𝑦 = P 𝑒 ,# 𝑑𝑥
𝑒I 𝑒I
1 2
𝑦 = ln R S 𝑦 = ln R S
𝑐0 − 𝑒 # 𝑐0 − 𝑒 ,#
45 46
𝑑𝑦 𝑒 J3# 𝑑𝑦 𝑒 J4I
= =
𝑑𝑥 𝑒 J4I 𝑑𝑥 𝑒 J,#
P 𝑒 J4I 𝑑𝑦 = P 𝑒 J3# 𝑑𝑥 P 𝑒 4I 𝑑𝑦 = P 𝑒 ,# 𝑑𝑥
1 3𝑒 3# 1
𝑦 = ln Y 3# Z 𝑦 = ln(𝑐0 + 2𝑒 ,# )
4 𝑐0 𝑒 + 4 4
47 48
𝑑𝑦 sin 𝑥 𝑑𝑦 cos 𝑥
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑦
P 𝑦 𝑑𝑦 = P sin 𝑥 𝑑𝑥 P 𝑦 𝑑𝑦 = P cos 𝑥 𝑑𝑥
𝑦 , = 𝑐0 − 2 cos 𝑥 𝑦 , = 𝑐0 + 2 sin 𝑥
49 50
𝑑𝑦 sin 2𝑥 𝑑𝑦 1
= sec 3𝑥 =
𝑑𝑥 2𝑦 𝑑𝑥 3𝑦
P 2𝑦 𝑑𝑦 = P sin 2𝑥 𝑑𝑥 P 3𝑦 𝑑𝑦 = P cos 3𝑥 𝑑𝑥
1 2
𝑦 , = 𝑐0 − cos 2𝑥 𝑦 , = 𝑐0 + sin 3𝑥
2 9
P sin 3𝑦 𝑑𝑦 = P 𝑒 3# 𝑑𝑥 P cos 8𝑦 𝑑𝑦 = P 𝑒 4# 𝑑𝑥
cos 3𝑦 = 𝑐0 − 𝑒 3# sin 8𝑦 = 𝑐0 + 2𝑒 4#
57 58
𝑑𝑦 sin, 𝑥 𝑑𝑦 cos , 𝑥
= =
𝑑𝑥 𝑦 𝑑𝑥 𝑦
P 𝑦 𝑑𝑦 = P sin, 𝑥 𝑑𝑥 P 𝑦 𝑑𝑦 = P cos , 𝑥 𝑑𝑥
1 1
𝑦 , = 𝑐0 + 𝑥 − sin 2𝑥 𝑦 , = 𝑐0 + 𝑥 + sin 2𝑥
2 2
59 60
𝑑𝑦 sin, 𝑥 𝑑𝑦
= sec , 𝑥 = cosec , 𝑦
𝑑𝑥 cos , 𝑦 𝑑𝑥
P 𝑦 , 𝑑𝑦 = P 4 sin, 2𝑥 𝑑𝑥 P 𝑦 3 𝑑𝑦 = P 6 cos , 3𝑥 𝑑𝑥
𝑦 4 = 𝑐0 + 12𝑥 + 2 sin 6𝑥
H 3
𝑦 = F𝑐0 + 6𝑥 − sin 4𝑥
2
63 64
𝑑𝑦 sec , 𝑥 𝑑𝑦 cos , 2𝑦
= =
𝑑𝑥 sec , 𝑦 𝑑𝑥 cos , 2𝑥
P 𝑦 𝑑𝑦 = P ln 𝑥 𝑑𝑥 P 𝑦 𝑑𝑦 = P 𝑥 ln 𝑥 𝑑𝑥
𝑦 , = 𝑐0 + 2𝑥 ln 𝑥 − 2𝑥 1
𝑦 , = 𝑐0 + 𝑥 , ln 𝑥 − 𝑥 ,
2
67 68
𝑑𝑦 𝑥 1 𝑑𝑦 10
= ,
= ,
𝑑𝑥 ln 𝑦 𝑥 𝑑𝑥 𝑦 ln 𝑦
P ln 𝑦 𝑑𝑦 = P 𝑥 𝑑𝑥 P 𝑦 , ln 𝑦 𝑑𝑦 = P 10𝑥 , 𝑑𝑥
1 3𝑥 3 ln 𝑥 − 𝑥 3 = 𝑐0 + 30𝑥 3
𝑦 ln 𝑦 − 𝑦 = 𝑐0 + 𝑥 ,
2
69 70
𝑑𝑦 𝑥 = ln 𝑥 𝑥 = 𝑑𝑦 𝑦3
= =
𝑑𝑥 𝑦 3 ln 𝑦 ln 𝑥 𝑑𝑥 ln 𝑦
ln 𝑦 ln 𝑥
P 𝑦 3 ln 𝑦 𝑑𝑦 = P 𝑥 = ln 𝑥 𝑑𝑥 P 3
𝑑𝑦 = P = 𝑑𝑥
𝑦 𝑥
36𝑦 4 ln 𝑦 − 9𝑦 4 = 𝑐0 + 24𝑥 ? ln 𝑥 − 4𝑥 ? 8 ln 𝑦 4 4 ln 𝑥 1
,
+ , = 𝑐0 + 4 + 4
𝑦 𝑦 𝑥 𝑥
H 3 T 5
𝑦 = F𝑐0 + (𝑥 + 1)4 𝑦 = F𝑐0 + (𝑥 + 2)?
4 6
75 76
𝑑𝑦 (2𝑥 − 3)4 𝑑𝑦
= (3𝑥 + 4)3 = (2𝑦 − 3)4
𝑑𝑥 (3𝑦 + 4)3 𝑑𝑥
1 1
P(3𝑦 + 4)3 𝑑𝑦 = P(2𝑥 − 3)4 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
(2𝑦 − 3)4 (3𝑥 + 4)3
77 78
𝑑𝑦 (4𝑥 + 5)? 𝑑𝑦
= (5𝑥 − 3)4 = (4𝑦 + 5)?
𝑑𝑥 (5𝑦 − 3)4 𝑑𝑥
1 1
P(5𝑦 − 3)4 𝑑𝑦 = P(4𝑥 + 5)? 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
(4𝑦 + 5)? (5𝑥 − 3)4
1 T 25 1 T 3(5𝑥 − 3)3
𝑦 = ] F𝑐0 + (4𝑥 + 5)V + 3^ 𝑦 = ]F − 5^
5 28 4 𝑐0 (5𝑥 − 3)3 + 4
79 80
𝑑𝑦 √𝑥 − 4 𝑑𝑦 E𝑦 − 4
= =
𝑑𝑥 𝑦3 𝑑𝑥 𝑥3
1 1
P 𝑦 3 𝑑𝑦 = P √𝑥 − 4 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
E𝑦 − 4 𝑥3
8 3
𝑦 4 = 𝑐0 + (𝑥 − 4), 1 ,
3 𝑦 = R𝑐0 − , S + 4
4𝑥
1 1
P 𝑦 4 𝑑𝑦 = P √2𝑥 − 5 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
E2𝑦 − 5 𝑥4
1 1 ,
T 5 3
𝑦 = YR𝑐0 − 3 S + 5Z
𝑦 = F𝑐0 + (2𝑥 − 5), 2 3𝑥
3
83 84
𝑑𝑦 𝑦 𝑑𝑦
= 𝑥 = (𝑦 + 1)(𝑦 + 2)
𝑑𝑥 (𝑥 + 1)(𝑥 + 2) 𝑑𝑥
1 1 1 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
𝑦 (𝑥 + 1)(𝑥 + 2) (𝑦 + 1)(𝑦 + 2) 𝑥
𝑐0 (𝑥 + 1) 2𝑐0 𝑥 − 1
𝑦= 𝑦=
𝑥+2 1 − 𝑐0 𝑥
85 86
𝑑𝑦 𝑑𝑦
(𝑥 + 2)(𝑥 + 3) = 𝑦, 𝑥, = (𝑦 + 2)(𝑦 + 3)
𝑑𝑥 𝑑𝑥
1 1 1 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P , 𝑑𝑥
𝑦 , (𝑥 + 2)(𝑥 + 3) (𝑦 + 2)(𝑦 + 3) 𝑥
1 0
𝑦= 3𝑐0 𝑒 J# − 2
𝑥+2 𝑦=
𝑐0 − ln _𝑥 + 3` 0
1 − 𝑐0 𝑒 J#
87 88
𝑑𝑦 12𝑦 3 𝑑𝑦 (𝑦 + 1)(𝑦 + 4)
= =
𝑑𝑥 (𝑥 + 1)(𝑥 + 4) 𝑑𝑥 18𝑥 4
1 12 1 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
𝑦 3 (𝑥 + 1)(𝑥 + 4) (𝑦 + 1)(𝑦 + 4) 18𝑥 4
0
1 J
𝑦, = 4𝑐0 𝑒 0D# H −1
𝑥+1 𝑦= 0
𝑐0 − 8 ln _𝑥 + 4` J
1 − 𝑐0 𝑒 0D# H
89 90
𝑑𝑦 𝑥 − 17 𝑑𝑦
= 𝑥(𝑦 − 17) = (𝑦 − 3)(𝑦 + 4)
𝑑𝑥 (𝑥 − 3)(𝑥 + 4)𝑦 𝑑𝑥
𝑥 − 17 𝑦 − 17 1
P 𝑦 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 𝑑𝑥
(𝑥 − 3)(𝑥 + 4) (𝑦 − 3)(𝑦 + 4) 𝑥
1 8𝑥 + 1 32𝑦 − 6 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 3# 𝑑𝑥
𝑒 ,I 𝑥 (2𝑥 − 1) 𝑦(4𝑦 − 1) 𝑒
1 1 1
𝑦 = ln R S 6 ln 𝑦 + 2 ln(4𝑦 − 1) = 𝑐0 −
2 𝑐0 − 10 ln(2𝑥 − 1) + 2 ln 𝑥 3𝑒 3#
93 94
𝑑𝑦 8𝑥 , + 25𝑥 + 27 𝑑𝑦 𝑥 , 𝑦 , (𝑦 + 1)
= = ,
𝑑𝑥 𝑥(𝑥 + 3), 𝑒 4I 𝑑𝑥 5𝑦 − 6𝑦 − 9
8𝑥 , + 25𝑥 + 27 5𝑦 , − 6𝑦 − 9
P 𝑒 4I 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 𝑥 , 𝑑𝑥
𝑥(𝑥 + 3), 𝑦 , (𝑦 + 1)
1 32 9 1
𝑦 = ln R𝑐0 + 12 ln 𝑥 + 20 ln(𝑥 + 3) + S 3 ln 𝑦 + + 2 ln(𝑦 + 1) = 𝑐0 + 𝑥 3
4 𝑥+3 𝑦 3
95 96
𝑑𝑦 𝑑𝑦 (𝑦 − 6)(𝑦 + 1)(𝑦 + 2)
(𝑥 − 3)(𝑥 + 2)(𝑥 + 5) = 24(𝑥 + 7) sec 𝑦 =
𝑑𝑥 𝑑𝑥 (79𝑦 + 198) cosec 𝑥
1 13𝑥 + 46 15𝑦 − 5 1
P 𝑑𝑦 = P 𝑑𝑥 P 𝑑𝑦 = P 3 𝑑𝑥
E4𝑦 − 5 (𝑥 + 7)(2𝑥 + 5) (𝑦 − 3)(3𝑦 − 4)
(8𝑥 − 5)=
1 5 ,
𝑦 = ((𝑐0 + 10 ln(𝑥 + 7) + 3 ln(2𝑥 + 5)), + 5) 8 ln(𝑦 − 3) − 3 ln(3𝑦 − 4) = 𝑐0 + (8𝑥 − 5)=
4 16
99 100
𝑑𝑦 (90𝑥 + 140)𝑒 I 1 𝑑𝑦 (4 − 13𝑦 − 35𝑦 , ) sin 8𝑥
= =
𝑑𝑥 𝑦(20 + 9𝑥 − 18𝑥 , ) 𝑥 , 𝑑𝑥 40 − 11𝑦
𝑦 1 5 20 12 7
+ I = 𝑐0 − ln(6𝑥 + 5) + ln(4 − 3𝑥) ln(7𝑦 + 4) − ln(1 − 5𝑦) = 𝑐0 − 𝑥 , cos 𝑥 + 2𝑥 sin 𝑥 + 2 cos 𝑥
𝑒 I 𝑒 3 3 7 5